Dissenting traditions : essays on Bryan D. Palmer, Marxism, and history - Carleton, Sean; McCoy, Ted, 1978-; Smith, Julia, 1982- (Working Canadians (Edmonton, Alta.), 2021)
"The work of Bryan D. Palmer, one of North America's leading historians, has influenced the fields of labour history, social history, discourse analysis, communist history, and Canadian history, as well as the theoretical frameworks surrounding them. Palmer's work reveals a life dedicated to dissent and the difficult task of imagining alternatives by understanding the past in all of its contradictions, victories, and failures. Dissenting Traditions gathers Palmer's contemporaries, students, and sometimes critics to examine and expand on the topics and themes that have defined Palmer's career, from labour history to Marxism and communist politics. Paying attention to Palmer's participation in key debates, contributors demonstrate that class analysis, labour history, building institutions, and engaging the public are vital for social change. In this moment of increasing precarity and growing class inequality, Palmer's politically engaged scholarship offers a useful roadmap for scholars and activists alike and underlines the importance of working-class history."--